Análise da proteção de citocinas após exposição celular in vitro com os antígenos ML2478 e ML0840 do Mycobacterium leprae - MESSIAS, Ana Caroline Cunha (Universidade Federal do Pará, 2021)
Diagnosis of oligosymptomatic leprosy cases may enable interventions to be performed before the onset of physical disabilities. However, because the diagnosis is still essentially clinical and the disease progresses slowly, there is difficulty in recognizing these cases, since the lesions are discreets and with subtle changes in sensitivity. Most of the time patients are diagnosed when they already have obvious clinical characteristics and/or physical disabilities. Thus, is necessary to develop laboratory tools that help in the early diagnosis of the disease. The cell immunity assay Whole Blood Assay (WBA) is a low-cost, easy-to-perform technique that provides conditions for antigen screening and is favored in areas where leprosy is endemic and may facilitate incorporation of a test into sites with less access to sophisticated laboratories. The objective of this study was to evaluate the cellular immune response after in vitro exposure of peripheral blood to Mycobacterium leprae antigens ML2478 and ML0840. Eighty-seven individuals were selected for quantitation the cytokines of Interferon-γ (IFN-γ), Interleukin (IL)-10, IL-17 and Transforming Growth Factor-β1 after exposure with specific M. leprae antigens by WBA for 24 hours. A total of 47 leprosy cases were evaluated distributed in: 6 tuberculoid and 14 borderline tuberculoid, 13 borderline lepromatous leprosy, 6 lepromatous leprosy; and 8 schoolchildren diagnosed with leprosy during the group active search strategy (oligosymptomatic cases in the clinical forms: 1 primary neural, 1 undetermined, 6 borderline tuberculoid). The remaining 47 individuals corresponded to 20 contacts, 13 healthy schoolchildren and 7 individuals with other skin diseases. The analysis of cytokines suggests the balance between IFN-γ and IL-10 may indicate individuals who are progressing to the Th2 pole. IL-17 and TGF-β1 may be used to follow-up individuals with similar response to leprosy cases. The production of IFN-γ, IL-10, IL-17 and TGF-β1 cytokines by stimulation with proteins ML2478 and ML0840 did not differ between healthy students and case students. And the cytokine IL-17 demonstrated higher production in cases attended at URE than in case students and individuals in control groups.